1991
DOI: 10.1182/blood.v78.1.51.51
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hemophagocytic lymphohistiocytosis with chemotherapy and bone marrow transplantation: a single-center study of 22 cases

Abstract: Twenty-two children with hemophagocytic lymphohistiocytosis were treated with a chemotherapy regimen consisting of VP16–213, corticosteroids, and intrathecal methotrexate. A sustained clinical and biologic complete remission was obtained in 15 children and a partial remission in one child; six children died early of opportunistic infection (n = 4) or of disease progression (n = 2). Of the 16 children who were placed in first remission, 10 received maintenance chemotherapy alone, while six underwent bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…(5) Persistent disease activity at 2 months after start of HLH treatment appears to suggest a worse long-term prognosis. Fischer et al (1986) were the first to show that a cure for FHL could be achieved by SCT, as later confirmed by others (Todo et al, 1990;Blanche et al, 1991;Nespoli et al, 1991;Bolme et al, 1995;Baker et al, 1997;Jabado et al, 1997;Dürken et al, 1999;Imashuku et al, 1999b). Initially, only matched donors were used but, since the outcome of FHL is invariably fatal without a successful SCT, HLA non-identical donors are now used more often and represent a third of the donors in this analysis.…”
Section: Discussionmentioning
confidence: 62%
“…(5) Persistent disease activity at 2 months after start of HLH treatment appears to suggest a worse long-term prognosis. Fischer et al (1986) were the first to show that a cure for FHL could be achieved by SCT, as later confirmed by others (Todo et al, 1990;Blanche et al, 1991;Nespoli et al, 1991;Bolme et al, 1995;Baker et al, 1997;Jabado et al, 1997;Dürken et al, 1999;Imashuku et al, 1999b). Initially, only matched donors were used but, since the outcome of FHL is invariably fatal without a successful SCT, HLA non-identical donors are now used more often and represent a third of the donors in this analysis.…”
Section: Discussionmentioning
confidence: 62%
“…252 Several studies have demonstrated that HSCT is the only true hope for permanent control of the disease or essentially a cure. [253][254][255][256][257] A study of 86 children treated with HLH-94 followed by HSCT demonstrated similar long-term disease-free survival (70% at 3 years) with matched unrelated donor transplants as with matched sibling transplants. Survival with family haploidentical donor transplants or mismatched unrelated transplants showed much less favorable results with long-term disease-free survival of only 50%.…”
Section: Hsctmentioning
confidence: 99%
“…Although initial results appeared to be satisfactory , the current long-term observation has revealed frequent relapses and only 22·7% of patients enjoyed continuous disease-free survival, a result similar to that observed in FHL (Ambruso et al, 1980;Fisher et al, 1985). This experience suggests that a more intensive therapy, or bone marrow transplantation, as adopted currently in FHL treatment (Blanche et al, 1991;Jabado et al, 1996), should be applied to those relapsed patients or partial responders.…”
Section: Discussionmentioning
confidence: 99%